The multipartite Muse: sectioned composition in Hellenistic long poems - Bone, P (2021)
The field of Hellenistic poetry has seen many interesting developments in recent years, but a very basic feature shared by the long poems of the period has yet to be given the attention it deserves. This feature is the division of the texts into large numbers of clearly marked sections. An examination of the processes of ‘sectioning’ demonstrates how significant a role this aspect of composition plays in shaping our experience of the poems. Engaging with sections allows for a fuller appreciation of the poets’ achievements, and helps us to understand the potential appeal of those poets less well received (or less well noticed) by modern scholarship. The study of this feature takes us to questions of great literary importance in the Hellenistic world, and places this varied group of poems firmly at the centre of Hellenistic literary culture.